Canva AI as a Cognitive Partner in Arabic Writing Instruction: Enhancing Linguistic Expression and Communicative Competence through Magic Write - Arifah, Nurdiana; Mahdaf, Hesti Firdausi; Ni’matul Fitri, Dahlia Dwi; Veronica, Nila Ayu (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2026)
The integration of Artificial Intelligence (AI) into language learning has introduced new opportunities for developing writing skills beyond conventional grammar-focused instruction. This study investigates the role of Canva AI, particularly its Magic Write feature, in enhancing Arabic writing (Maharah Kitabah) among university students. Using a qualitative descriptive approach, the study analyzes the transformation of studentsâ€™ drafts into AI-assisted texts through documentation and content analysis. The primary data consist of Arabic writing products in the genres of condolence messages (ta’ziyah) and birthday greetings (yaumul milad), while relevant literature on AI-assisted writing and Arabic language learning serves as supporting data. The findings reveal that Canva AI contributes to Arabic writing development in two significant ways. First, it functions as a linguistic refinement tool by improving lexical choice, textual cohesion, pragmatic appropriateness, and stylistic quality. Second, it serves as an expressive enrichment tool by expanding semantic content, diversifying expressions, and enhancing the emotional and communicative dimensions of writing. The study further demonstrates that Canva AI operates not merely as a writing assistant but as a cognitive partner that supports students in producing more natural, contextually appropriate, and aesthetically appealing Arabic texts. These findings suggest that the integration of Generative AI into Arabic writing instruction can promote communicative competence, pragmatic awareness, and linguistic creativity while maintaining the learnerâ€™s central role in the writing process.